Comparative analysis of methods for testing web applications - Wojciech Superson; Tomasz Smyk; Małgorzata Plechawska-Wójcik (Journal of Computer Sciences Institute)
The aim of the study was to conduct a comparative analysis of testing approaches for web applications in the two most popular architectures: monolithic and microservices. For the purpose of the study, the server-side of the application (backend) was implemented twice with identical functionalities for each of these architectures, allowing for a precise comparison of testing differences for the same program capabilities. The results revealed that the monolithic application was easier and faster to test. However, the microservices architecture requires more energy spent on testing, but allows better scalability and elasticity for independent teams to develop applications. Each of the examined architectures certainly has its own advantages and drawbacks. Furthermore, the conducted research indicates that unit tests require significantly less time to execute. However, when it comes to comprehensive code analysis, integration tests outperform unit tests by covering a substantial portion of the application's code with a single test. Nonetheless, the best comprehensive code analysis and protection against unwanted functional changes can be achieved by employing all known types of tests.